Конфіденційна інформація, інформація про особу та персональні дані: співвідношення і розповсюдження - Похлєба, А. В. (ХНУРЕ, 2020)
In the Ukrainian legislation several laws regulate the provision of information about individuals and legal entities. These are the Law on Information, which regulates relations concerning the receipt and distribution of information, and the Law on Protection of Personal Data, which defines the protection and processing of personal data, and the Law on Access to Public Information, which grants the right to receive information, owned by the managers.The same definitions in these Laws are not identical but, at times, partly contradictory to one another, which creates problems for a person to exercise his right to information.
Keywords: філософія; конфіденційна інформація